Effects of tranexamic acid during endoscopic sinsus surgery in children - Ahmed A Eldaba; Yasser Mohamed Amr; Osama A Albirmawy (Saudi Journal of Anaesthesia, 2013)
Objectives: This study was conducted to evaluate the effect of tranexamic acid (TA) on the intra-operative bleeding during the functional endoscopic sinus surgery (FESS) in children. Methods: A total of 100 children recruited to undergo FESS were randomized into two groups. Group I: Was given just after induction, intra-venous 25 mg/kg TA diluted in 10 ml of normal saline. Group II: Was given 10 ml of normal saline. Non-invasive blood pressure, heart rate, and quality of the surgical field were estimated every 15 min. Volume of bleeding and duration of the surgical procedure were recorded. Results: Surgical field quality after 15 min revealed that seven patients in group I had minimal bleeding versus no one in group II, P=0.006. Meanwhile, 35 patients in group I had mild bleeding versus 26 patients in group II, P=0.064. Higher number of patients in group II than in group I had moderate bleeding, P=0006. Also, at 30 min, revealed that 10 patients in group I had minimal bleeding versus one patient in group II, P=0.004. Meanwhile, 37 patients in group I had mild bleeding versus 28 patients in group II, P=0.059. Higher number of patients in group II than in group I had moderate bleeding, P<0001. Duration of the surgeries and volume of bleeding were significantly less in tranexamic group than the placebo group, P<0.0001. Conclusion: Single intra-venous bolus dose of tranexamic in children during the FESS improves quality of surgical field, reduces intra-operative bleeding, and duration of surgery.